Bacterial Patterns and Antibiotic Sensitivity of Blood Culture Specimens in Neonatal Sepsis Patients - Ni Putu Meliningsih; Putu Ayu Parwati; Ni Luh Putu Thrisna Dewi (Jurnal Kesehatan Cendikia Jenius, 2026)
Background: Neonatal sepsis is a leading cause of morbidity and mortality in newborns. Variations in bacterial patterns and antibiotic susceptibility across hospitals necessitate microbiological surveillance as a basis for selecting appropriate empirical therapy. Objective: This study aims to determine the bacterial patterns and antibiotic susceptibility profiles in blood cultures of neonatal sepsis patients in the NICU of Buleleng District Hospital in 2025. Methods: A quantitative descriptive study with a retrospective approach and a cross-sectional design was conducted on 57 positive blood culture specimens using a total sampling technique. Data from January to December 2025 were analyzed descriptively using frequency distributions and percentages. Result: The results showed that Gram-negative bacteria were predominantly Klebsiella pneumoniae (64.9%), while the most common Gram-positive bacteria were Staphylococcus epidermidis and Staphylococcus hominis (3.5% each). All Gram-positive isolates were sensitive to doxycycline, vancomycin, and linezolid, but resistant to oxacillin, penicillin, and moxifloxacin. Conclusion: Neonatal sepsis in the NICU of Buleleng District Hospital was predominantly caused by Klebsiella pneumoniae, while Staphylococcus epidermidis and Staphylococcus hominis were the most frequently identified Gram-positive bacteria.